PERAN IMPLEMENTASI CORPORATE GOVERNANCE DALAM PENGUNGKAPAN SUSTAINABILITY REPORTING - Immanuel, Gilbert; Sambuaga, Elfina Astrella (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research aims to provide empirical evidence on the influence of the implementation of corporate governance on sustainability reporting disclosure. The governance components in this study focus on the presence, educational background, and frequency of board of commissioners, board of directors, and audit committee meetings that contribute to the establishment, implementation, and oversight of sustainability-related company policies. The research sample consists of 78 non-financial sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2020-2022, selected using a purposive sampling method. This research utilizes secondary data sources obtained from the official BEI website, the respective company websites, and S&P Capital IQ to fulfill the data completeness tested with a multiple linear regression model using SPSS application. The research results indicate that the size of the commissioners and the frequency of audit committee meetings have a positive impact on sustainability reporting disclosure. Meanwhile, the research proves that the size of independent commissioners, the size of the board of directors, the size of the audit committee, the educational background of commissioners, the educational background of independent commissioners, the educational background of directors, the frequency of board of commissioners’ meetings, and the frequency of board of directors meeting do not have a significant impact on sustainability reporting disclosure. The implications of this research can raise awareness among business stakeholders and regulators about the importance of the role of commissioners and the frequency of audit committee meetings in enhancing sustainability reporting practices.